2018
DOI: 10.3390/met8010058
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of TiB2-(Supra-Nano-Dual-Phase) High-Entropy Alloy Cermet by Spark Plasma Sintering

Abstract: This paper introduces the preparation method and characterization results of TiB 2 ceramics with CoCrFeNiAl high-entropy alloy (HEA) as a sintering aid by Spark Plasma Sintering (SPS). Good wettability between HEA and TiB 2 was proved by the sessile drop method, indicating promising prospects for this composite. The sintering results showed that the addition of HEA could dramatically promote the sinterability of TiB 2 . TiB 2 -5 wt. % HEA dense ceramics prepared at the optimal temperature of 1650 • C showed fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…In general, porosity and grain size have a primary effect on the bending strength of a material. 14),19), 38) Equations (2) and 3) 28, 29) describes the relationship between the bending strength and porosity and grain size of a material:…”
Section: Morphology and Phase Constituents Of The Powdersmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, porosity and grain size have a primary effect on the bending strength of a material. 14),19), 38) Equations (2) and 3) 28, 29) describes the relationship between the bending strength and porosity and grain size of a material:…”
Section: Morphology and Phase Constituents Of The Powdersmentioning
confidence: 99%
“…Wu et al 28) studied TiB 2 30 wt % (FeNi) composite cermets, and the fracture toughness was 19.26 « 0.72 MPa m 1/2 . Zhang et al 29) fabricated TiB 2 5 wt % CoCrFeNiAl HEAs composite cermets with a hardness and flexural strength of 2386 « 18 HV 5 and 820 « 9 MPa, respectively. The research results showed that the CoCrFeNiAl HEAs possess outstanding wettability to TiB 2 ceramics, which is the linchpin to reaching superior properties in a ceramic material.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the CoCrFeMnNi alloy [7] showed excellent fracture resistance even at cryogenic temperatures [8,9]. Using HEA binders, several cermet materials have been obtained, including WC-CoCrFeNiMn [10], Ti(C,N)-CoCrFeNiAl [11,12], TiB2-CoCrFeNiTiAl [13,14], TiB2-CoCrFeNiAl [15], and TiB2-TiC-CoCrFeNiTiAl [15]. It was suggested that such materials gave birth to a new family of cermets [17].…”
Section: Introductionmentioning
confidence: 99%
“…The high-entropy alloys (HEA) have many advantages, such as, high hardness, wear resistance, strength and corrosion resistance, good softening resistance during tempering, and so on [1][2][3][4][5][6]. Therefore, the HEA could be used in many fields.…”
Section: Introductionmentioning
confidence: 99%